The Influence of Competency Development and Change Readiness on Public Sector Performance Mediated by Organizational Culture - Nur Ikhwan Kurnia; Eka Yudhyani; Sayid Irwan (Jurnal Ilmiah Manajemen Kesatuan, 2026)
Public sector organizations in Indonesia are striving to become more agile and responsive amid rapid technological change and increasing public expectations, yet institutional inertia and resistance to change often hinder successful administrative transformation. This study examines the influence of competency development, organizational change readiness, and organizational culture on organizational performance at the Class I Immigration Office of TPI Samarinda during its transition period. The research investigates the direct effects of competency development and organizational change readiness on performance, along with the mediating role of organizational culture. Data were collected through a survey from 67 purposively selected employees and analyzed using partial least squares structural equation modeling. Findings indicate that competency development and organizational change readiness have significant positive direct effects on organizational performance. Organizational culture positively influences performance and partially mediates the relationship between competency development and performance. However, it does not mediate the link between organizational change readiness and performance, showing that readiness can drive results independently. These results underscore the need to invest in employee skill enhancement and change readiness to improve service quality and efficiency. Managers should focus on competency programs and supportive communication while building an adaptive organizational culture for effective and sustainable public sector transformation.